PENERAPAN NILAI CINTA KASIH PADA ANAK KELOMPOK B DI TK SUSTER PONTIANAK KOTA - Evil Gasela Tutut; Muhamad Ali; Lukmanulhakim Lukmanulhakim (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2021)
AbstractThis study aims to determine the application of the value of love to group B children in Kindergarten Suster Pontianak Kota. The method used is descriptive with a qualitative research form. The data source of this research is groups B1, B2, B3 and B4 and the data is to form children with good personalities and behave according to applicable norms such as accustoming children to apply the value of love through patient, polite, caring and forgiving behavior, but there are still children who not applying the value of love, such as not being able to stand in line when washing hands, not greeting teachers when they come and go home from school, not throwing garbage in its place, and not wanting to forgive their friends. The results of the appointment research in the application of the values of teacher love have provided good directions. This is evidenced by 107 children from B1 to B4, there are 10 children who still need guidance and direction in applying the value of love so that children get used to applying the value of love both at home and at school.Keywords: Value of Love and Application